Pembangunan Perangkat Lunak IT Mentoring Berbasis Website pada Program Studi Informatika Kalbis Institute - Ivan Surya; Yulia Ery Kurniawati (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
The research object to develop a web IT Mentoring application at the Informatics Department, Kalbis Insitute. The software development method used to develop applications is Rapid Application Developer (RAD) with software modeling using the Unified Modeling Language (UML). The application is built using Sublime Text 3 with HTML, CSS, JavaScript, PHP, and Mysql programming languages to build website applications. The results of the User Experience testing test get IT Mentoring based on a website at Informatics Department, Kalbis Insitute that is easy to use. The result of the Black Box Testing test show that every test carried out is as expected.